Pengaruh Sistem Pengendalian Intern dan Keputusan Pemberian Kredit Dengan Peran Pemeriksa Internal Sebagai Variabel Mediasi Pada Bank Pemerintah di Kota Ambon - Pesireron, Semy; Sipakoly , Selly; Patty, Junus (Journal of Applied Accounting, 2023)
This research aims to empirically test the influence of the role of internal auditors in mediating the influence of the internal control system on credit granting decisions at Government Banks in Ambon City. The research data collection technique is a survey by distributing questionnaires to respondents selected based on sampling techniques. The sampling technique in this research was carried out using a purposive sampling method, namely, sampling with research considerations. The analysis technique used is mediation variable regression analysis, with a significance level used of 0.05 or 5%. The results of the study show that the role of internal auditors mediates the relationship between the internal control system and credit granting decisions.Keywords: Internal Control System, Credit Granting, Role of Internal Auditors